On the class of square Petrie matrices induced by cyclic permutations - Bau-Sen Du (International Journal of Mathematics and Mathematical Sciences)
Let n≥2 be an integer and let P={1,2,…,n,n+1}. Let Zp denote the finite field {0,1,2,…,p−1}, where p≥2 is a prime. Then every map σ on P